2006
DOI: 10.1161/circulationaha.105.593038
|View full text |Cite
|
Sign up to set email alerts
|

Proarrhythmic Potential of Mesenchymal Stem Cell Transplantation Revealed in an In Vitro Coculture Model

Abstract: Background-Mesenchymal stem cells (MSCs) are bone marrow stromal cells that are in phase 1 clinical studies of cellular cardiomyoplasty. However, the electrophysiological effects of MSC transplantation have not been studied. Although improvement of ventricular function would represent a positive outcome of MSC transplantation, focal application of stem cells has the potential downside of creating inhomogeneities that may predispose the heart to reentrant arrhythmias. In the present study we use an MSC and neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
173
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 56 publications
9
173
3
2
Order By: Relevance
“…This heterogeneity effect is clearly documented in vitro using co-cultures of cells of interest and neonatal rat cardiomyocytes [87,88]. As an example one can cite a doseresponse study that examined MSC and rat neonatal myocyte networks, and observed delayed conduction velocities and an increased inducibility of reentrant arrhythmias by highfrequency stimulation [87]. These effects occurred despite the presence of functional gap junctions, functionality of which was confirmed by a dye transfer technique, and was attributed to the presence of unexcitable MSC.…”
Section: Incomplete Coupling and Ensuing Heterogeneity Pose A Risk Ofmentioning
confidence: 93%
See 1 more Smart Citation
“…This heterogeneity effect is clearly documented in vitro using co-cultures of cells of interest and neonatal rat cardiomyocytes [87,88]. As an example one can cite a doseresponse study that examined MSC and rat neonatal myocyte networks, and observed delayed conduction velocities and an increased inducibility of reentrant arrhythmias by highfrequency stimulation [87]. These effects occurred despite the presence of functional gap junctions, functionality of which was confirmed by a dye transfer technique, and was attributed to the presence of unexcitable MSC.…”
Section: Incomplete Coupling and Ensuing Heterogeneity Pose A Risk Ofmentioning
confidence: 93%
“…This negative outcome was the main reason for discontinuation of early clinical trials which employed skeletal myoblasts [24]. This heterogeneity effect is clearly documented in vitro using co-cultures of cells of interest and neonatal rat cardiomyocytes [87,88]. As an example one can cite a doseresponse study that examined MSC and rat neonatal myocyte networks, and observed delayed conduction velocities and an increased inducibility of reentrant arrhythmias by highfrequency stimulation [87].…”
Section: Incomplete Coupling and Ensuing Heterogeneity Pose A Risk Ofmentioning
confidence: 99%
“…This intermediate level of complexity between cell and tissue provides a quantitative biophysical model that is experimentally accessible to reproducible conditions such as different forms of mechanical perturbations. Unlike conventional tissue preparations, the two dimensional (2-D) monolayer structure can be controlled using methods of tissue engineering to direct the pattern of cell growth (via engineered surfaces and substrates) (Rohr et al, 1991;Bursac et al, 2002) and the composition of cell types (Abraham et al, 2005;Chang et al, 2006), so that potentially, the mechanosensitivity of different cell types or mixtures can be characterized. Because the 2-D cell culture allows rapid superfusion and control of the extracellular environment, they are well suited for detailed biophysical experiments, especially when applying different drugs or molecular interventions to identify signaling pathways of interest in MEF.…”
Section: Why Use a Cultured Cell Monolayer?mentioning
confidence: 99%
“…A few investigators have used in vitro coculture model systems [18]- [20] to study the interaction of donor cells with cardiomyocytes. Although some valuable insights were gained through these systems, the applied culture methods lacked reproducibility in the spatial distribution of cocultured cells or potentially introduced cell injury, both of which may render the systematic studies and interpretation of the results difficult.…”
Section: Introductionmentioning
confidence: 99%